1982
DOI: 10.1073/pnas.79.23.7425
|View full text |Cite
|
Sign up to set email alerts
|

Mutant immunoglobulin genes have repetitive DNA elements inserted into their intervening sequences.

Abstract: The K light chain genes from two mutant hybridoma cell lines defective in K light chain synthesis were isolated and compared to the wild-type K light chain gene. In each case, the mutant K light chain genes-were found to contain repetitive DNA elements-in their intervening sequences that were not present in the intervening sequences of the wild-type K light chain gene. These elements were found to be related to the genes of intracisternal A particles. These results suggest that the decreased production of K li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
78
0
1

Year Published

1984
1984
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(85 citation statements)
references
References 44 publications
6
78
0
1
Order By: Relevance
“…They do not exclude the possibility that a small fraction of p73 is generated by cleavage of the larger polypeptides. IAP genes are abundantly reiterated in the mouse DNA (28,34) and have the capability of transposing to new locations in the genome (5,7,9,10,18,19,40 Our results are relevant to the known IAP expression in early mouse development. Yotsuyanagi and Szollosi (46) have recently shown that large IAPs typical of those seen in mouse tumors are present in ovarian oocytes but disappear progressively during oocyte maturation, fertilization, and early cleavage.…”
Section: Methodsmentioning
confidence: 62%
See 1 more Smart Citation
“…They do not exclude the possibility that a small fraction of p73 is generated by cleavage of the larger polypeptides. IAP genes are abundantly reiterated in the mouse DNA (28,34) and have the capability of transposing to new locations in the genome (5,7,9,10,18,19,40 Our results are relevant to the known IAP expression in early mouse development. Yotsuyanagi and Szollosi (46) have recently shown that large IAPs typical of those seen in mouse tumors are present in ovarian oocytes but disappear progressively during oocyte maturation, fertilization, and early cleavage.…”
Section: Methodsmentioning
confidence: 62%
“…and yeasts (8a). Recently, IAP genes have been found to appear in novel locations in the genome of certain IAP-rich BALB/c mouse myeloma and hybridoma cell lines and to affect the function of genes at the various target sites (5,7,9,10,18,19,41). Thus, on occasion they can act as mobile elements to provide a source of genetic variability in mouse cells.…”
mentioning
confidence: 99%
“…IAP-like sequences represent about 0.3% of chromosomal DNA in mice or 1000 copies (Lueders et. al., 1977, Hawley et. al.…”
Section: : Recombinational Ecologies In Retrotransposons and Retrovirmentioning
confidence: 99%
“…Many different mutations including down, up and regulatory mutations in yeasts are induced by a Ty-I insertion [69]. Mutations induced by IAP gene insertions are described in the vertebrates [70].…”
Section: Many Spontaneous Mutations Are Induced By Mobile Elementsmentioning
confidence: 99%